Atividade física, qualidade de vida e medicamentos em idosos: Diferenças entre idade e gênero - Sebastião, Émerson; Christofoletti, Gustavo; Gobbi, Sebastião; Hamanaka, Ágata Yoko Yasue; Gobbi, Lilian Teresa Bucken (FapUNIFESP (SciELO), 2009)
Studies have shown an inverse relationship between physical activity level (PAL), quality of life (QoL) and use of medications in the elderly. The objective of this study was to analyze possible relationships and differences between PAL, QoL and use of medications in the elderly. A total of 192 subjects (≥ 60 years) were selected by stratified random sampling according to census sector. The following assessment instruments were used: a) Modified Baecke Questionnaire for older adults, b) Medical Outcomes Study - 36-Item Short Form Health Survey, and c) Sociodemographic and Health Factors Questionnaire. Descriptive statistics and parametric and nonparametric tests were used (p<0.05). a) With respect to chronological age, significant differences between groups were only observed for PAL, with G1 (60-69 years) being more active than the other groups. b) With respect to gender irrespective of age, analysis showed a difference in QoL and in the number of medications, with men reporting better perceived QoL and using fewer medications. c) With respect to gender but considering chronological age, differences in PAL, QoL and medication use were observed between genders for specific age groups. In conclusion, in the elderly a) PAL is low, declines even more during advanced age and is higher in men than in women during the first decade of old age, and b) men report better perceived QoL and use fewer medications than women.
Physical activity, quality of life and medication in aging: Differences between age and gender
Keywords: Aging; Medication; Physical activity; Quality of life